Molecular basis for the preferential recognition of β1, 3‐1, 4‐glucans by the family 11 carbohydrate‐binding module from Clostridium thermocellum. (19th December 2019) - Ribeiro, Diana O.; Viegas, Aldino; Pires, Virgínia M. R.; Medeiros‐Silva, João; Bule, Pedro; Chai, Wengang; Marcelo, Filipa; Fontes, Carlos M. G. A.; Cabrita, Eurico J.; Palma, Angelina S.; Carvalho, Ana Luísa
Abstract : Understanding the specific molecular interactions between proteins and β1, 3‐1, 4‐mixed‐linked d ‐glucans is fundamental to harvest the full biological and biotechnological potential of these carbohydrates and of proteins that specifically recognize them. The family 11 carbohydrate‐binding module from Clostridium thermocellum ( Ct CBM11) is known for its binding preference for β1, 3‐1, 4‐mixed‐linked over β1, 4‐linked glucans. Despite the growing industrial interest of this protein for the biotransformation of lignocellulosic biomass, the molecular determinants of its ligand specificity are not well defined. In this report, a combined approach of methodologies was used to unravel, at a molecular level, the ligand recognition of Ct CBM11. The analysis of the interaction by carbohydrate microarrays and NMR and the crystal structures of Ct CBM11 bound to β1, 3‐1, 4‐linked glucose oligosaccharides showed that both the chain length and the position of the β1, 3‐linkage are important for recognition, and identified the tetrasaccharide Glcβ1, 4Glcβ1, 4Glcβ1, 3Glc sequence as a minimum epitope required for binding. The structural data, along with site‐directed mutagenesis and ITC studies, demonstrated the specificity of Ct CBM11 for the twisted conformation of β1, 3‐1, 4‐mixed‐linked glucans. This is mediated by a conformation–selection mechanism of the ligand in the binding cleft through CH‐π stacking and a hydrogen bonding network, which is dependent not only on ligand chain length, but also on the presence of a β1, 3‐linkage at the reducing end and at specific positions along the β1, 4‐linked glucan chain. The understanding of the detailed mechanism by which Ct CBM11 can distinguish between linear and mixed‐linked β‐glucans strengthens its exploitation for the design of new biomolecules with improved capabilities and applications in health and agriculture. Database: Structural data are available in the Protein Data Bank under the accession codes 6R3M and 6R31 . Abstract : The family 11 carbohydrate‐binding module (CBM) from Clostridium thermocellum is an archetypal example of carbohydrate‐binding modules binding to mixed‐linked glucans with a preference for β1, 3‐1, 4‐glucans. The analysis of this interaction by carbohydrate microarrays, nuclear magnetic resonance (NMR) and X‐ray crystallography has established the molecular basis of this unique recognition mechanism, including the distinction between linear and twisted mixed‐linked β‐glucans, inspiring the design of new biomolecules with applications in health and agriculture.